Young Cam Jansen and the pizza shop mystery - Adler, David A.; Natti, Susanna (New York : Puffin, 2001)
When Cam, her friend Eric, and her father stop for pizza while they are at the mall, Cam must rely on her photographic memory to locate her missing jacket.
School Library Journal, May 2000
Booklist, April 2000
Library Talk, January 2001
2.8
K-3
K-3
Keywords: Jansen, Cam (Fictitious character) -- Juvenile fiction; Memory -- Juvenile fiction; Lost articles -- Juvenile fiction; Jansen, Cam (Fictitious character) -- Fiction; Memory -- Fiction; Lost and found possessions -- Fiction; Mystery and detective stories; Jansen, Cam (Fictional character) -- Fiction; Memory -- Fiction; Lost and found possessions -- Fiction; Mystery fiction; Mystery fiction; Readers (Elementary)